The role of microRNAs in tumors - Liu, Chuanxin (Archives of pharmacal research, 2013)
The cancers are a series of serious diseases in the world, and the mechanism involved in many cancers has not yet been fully elucidated. Therefore, it is a very major and significant to explore the molecular mechanisms of cancer occurence and development. MicroRNAs (miRNAs), a class of molecules that regulates gene at post-transcription expression, play an important role in tumorigenesis. It has been proved that a number of miRNAs identified as aberrantly expressed during cancer development. In addition, some of the miRNAs may have prognostic significance. It is the aim of this review to describe the important role of miRNAs in cancer initiation and development as predictive, diagnostic, prognostic biomarkers and novel therapeutic strategies.